Pelaksanaan Baby Gym sebagai Upaya Menstimulasi Perkembangan Motorik Kasar pada Bayi Usia 3-4 Bulan - Susmita Susmita; Tri Restu Handayani (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
WHO states that globally, 52.9 million children younger than 5 years old are experiencing developmental problems. Data on child development services in Indonesia shows that as many as 7.5% experience delays in growth and development. One effort to stimulate baby development is to do a baby gym. Baby gym is movement or physical exercise for babies aged > 3 months which aims to stimulate gross motor development. The aim of this community service activity is to increase the knowledge and skills of baby mothers in stimulating gross motor development by carrying out various baby gym exercises and movements. This activity was carried out at PMB Andina Palembang involving 10 activity participants, namely mothers and babies aged 3-4 months. The results of community service activities showed that there was an increase in the average knowledge of activity participants before and after implementing the baby gym education, where the pretest average was 40.2 and the posttest average was 82.0. It is hoped that all parties can work together to increase knowledge and motivation to carry out baby gym regularly.